Semi-automatic Extraction of Functional Dynamic Networks Describing Patient's Epileptic Seizures - Frusque, Gaëtan; Borgnat, Pierre; Gonçalves, Paulo; Jung, Julien (Frontiers in Neurology, 2020)
Intracranial EEG studies using stereotactic EEG (SEEG) have shown that during seizures, epileptic activity spreads across several anatomical regions from the seizure onset zone towards remote brain areas. A full and objective characterisation of this patient-specific time-varying network is crucial for optimal surgical treatment. Functional Connectivity (FC) analysis of SEEG signals recorded during seizures enables to describe the statistical relations between all pairs of recorded signals. However, extracting meaningful information from those large datasets is time-consuming and requires high expertise. In the present study, we first propose a novel method named Brain-wide Time-varying Network Decomposition (BTND) to characterise the dynamic epileptogenic networks activated during seizures in individual patients recorded with SEEG electrodes. The method provides a number of pathological FC subgraphs with their temporal course of activation. The method can be applied to several seizures of the patient to extract reproducible subgraphs. Secondly, we compare the activated subgraphs obtained by the BTND method with visual interpretation of SEEG signals recorded in 27 seizures from 9 different patients. As a whole, we found that activated subgraphs corresponded to brain regions involved during the course of the seizures and their time course were highly consistent with classical visual interpretation. We believe that the proposed method can complement the visual analysis of SEEG signals recorded during seizures by highlighting and characterising the most significant parts of epileptic networks with their activation dynamics.